A Quadrature Single Side-Band Mixer with Passive Negative Resistance in Software-Defined Frequency Synthesizer - Dongsheng Liu; Ang Hu; Kefeng Zhang (Sensors, 2018)
Software-defined radio (SDR) is a good solution for complying with the existing and incoming protocols for emerging wireless sensor networks (WSN) and internet of things (IoT) applications. The frequency synthesizer in a SDR tranceiver usually consists of a phase locked loop (PLL) and a post synthesizer. The PLL is the narrow band signal source and the post synthesizer generates wideband outputs by mixing and dividing. Compared with a frequency synthesizer utilizing the wideband PLL, this synthesizer features relatively constant loop parameters and mitigates the requirement for the oscillator. In this paper, a quadrature single side-band (QSSB) mixer with the proposed passive negative resistance (PNR) for frequency mixing in a post synthesizer is presented. The PNR is achieved by biasing the Metal-Oxide-Semiconductor Field-Effect Transistors (MOSFET) of the cross-coupled pair at the deep-triode region periodically and incorporates an inductor and a cap-array as the mixer load. Compared with the traditional single side-band mixers utilizing Inductor-Capacitor (LC) resonant loads or quality factor enhanced (Q-enhanced) LC resonant loads, which suffer from a selectivity versus working range trade-off, the mixer employing the proposed loading structure provides not only a wide operating range, but also a superior image side-band rejection ratio (ISRR). Moreover, the oscillating risk in conventional mixers adopting Q-enhanced LC resonant loads is eliminated. A wideband frequency synthesizer employing the proposed mixer was implemented in a TSMC 0.18 µm CMOS process and the mixer performed ISRR of 40–57 dB and 30–57 dB across 2.5–3 GHz and 2.3–3.2 GHz, respectively. The power consumption of the QSSB mixer, including buffer, is 18 mA from a 1.8 V supply and the active area is 0.445 mm2. The measurement results provide validation that the proposed QSSB mixer is suitable for wideband software-defined frequency synthesizers and other frequency generating systems.